Association between digital health literacy and antenatal care adherence among pregnant women - Hernia Novianti; Sri Wahyuni; Eka Lestari Sitepu (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Pregnancy is a critical period that affects the health of both the mother and the fetus. Antenatal Care (ANC) plays an important role in the early detection of pregnancy complications, however, adherence to the recommended ANC visit schedule remains a challenge. Digital health literacy is increasingly important in supporting health-related decision-making among pregnant women. Purpose: To examine the association between digital health literacy and adherence to Antenatal Care (ANC) visits among pregnant women. Method: This study employed an analytic observational design with a cross-sectional approach. The study was conducted in three villages in Silih Nara District, Aceh Tengah Regency, from May to June 2026. The population comprised all pregnant women who underwent examinations at Posyandu during the study period. A total sampling technique was used, resulting in a sample of 38 pregnant women. Digital health literacy was measured using the eHealth Literacy Scale (eHEALS), and adherence to ANC visits was assessed through verification of the Maternal and Child Health Book and ANC visit records at the Community Health Center. Data were analyzed using the Chi-square test to determine the association between digital health literacy and adherence to ANC visits. Results: The average age of respondents was 29.52 years (SD ± 6.49), with the majority having completed secondary education (52.63%). Most respondents' mothers were working (78.95%). The mean distance from respondents' homes to the nearest health facility was 5.78 km (SD ± 3.05). Based on the Chi-square test, a p-value of 0.002 was obtained, indicating a statistically significant association between digital health literacy and adherence to ANC visits. In the non-adherent group, 10.00% had low digital health literacy, 16.67% had moderate literacy, and 36.84% had high literacy. In contrast, in the adherent group, 90.00% were classified in the low literacy category, 83.33% in the moderate category, and 31.25% in the high category. Conclusion: Digital health literacy was significantly associated with adherence to Antenatal Care (ANC) visits among pregnant women. Pregnant women with better digital health literacy tended to demonstrate higher adherence to recommended ANC schedules. Suggestion: It is recommended that health facilities and community health workers provide education to the public regarding the understanding and benefits of digital health literacy in supporting Antenatal Care (ANC) adherence. Enhancing community knowledge in this area will contribute to the implementation of maternal and child health programs as a preventive effort against pregnancy complications and poor birth outcomes.